Evaluasi Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) di Dinas Komunikasi dan Informatika Kota Padang - Santy Hidayatullah; Sisri Nadia Adha; Regina Olivia; Refa Hidayahtunnisa; Yulia Hanoselina; Yuliarti Y (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Progress in information and communication technology has propelled digital transformation in governmental administration to enhance efficiency, transparency, and the quality of public services. The Indonesian government intends to do this through the implementation of an Electronic-Based Government System (ESBS). This study is to assess the efficacy of the ESBS installation at the Padang City Communication and Informatics Office and to identify factors affecting its performance in promoting good governance. This study is grounded in e-government theory. The employed methodology is a descriptive qualitative approach. The findings demonstrate that the introduction of ESBS has positively influenced administrative efficiency, enhanced internal coordination, and elevated the quality of digital public services. The implementation remains unsatisfactory due to various constraints, including inadequate integration across Regional Apparatus Organisations (OPD), low human resource capacity, insufficient digital literacy within the community, and compromised system security. Consequently, strengthening system integration, augmenting human resource competencies, and instituting ongoing assessment are essential for optimising ESBS to attain effective and sustainable governance.